2009
DOI: 10.1371/journal.ppat.1000264
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Lignin Biosynthesis Promotes the Sexual Reproduction of Homothallic Oomycete Pathogens

Abstract: Lignin is incorporated into plant cell walls to maintain plant architecture and to ensure long-distance water transport. Lignin composition affects the industrial value of plant material for forage, wood and paper production, and biofuel technologies. Industrial demands have resulted in an increase in the use of genetic engineering to modify lignified plant cell wall composition. However, the interaction of the resulting plants with the environment must be analyzed carefully to ensure that there are no undesir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 64 publications
3
73
0
1
Order By: Relevance
“…The susceptibility of comt mutants is independent of hormone-mediated defenses and correlates with a signifi cant decrease in sinapoyl malate, a hydroxycinnamate ester also derived from the phenylpropanoid pathway (D'Auria and Gershenzon, 2005;Quentin et al, 2009). Plant treatment with fl g22, harpins, and necrosis-inducing Phytophthora protein 1 (NPP1) induces COMT expression suggesting it may function in PTI (Quentin et al, 2009). Several other hydroxycinnamate derivatives functioning in resistance to A. brassicicola were also recently described (Muroi et al, 2009).…”
Section: Phytoalexins and Other Secondary Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The susceptibility of comt mutants is independent of hormone-mediated defenses and correlates with a signifi cant decrease in sinapoyl malate, a hydroxycinnamate ester also derived from the phenylpropanoid pathway (D'Auria and Gershenzon, 2005;Quentin et al, 2009). Plant treatment with fl g22, harpins, and necrosis-inducing Phytophthora protein 1 (NPP1) induces COMT expression suggesting it may function in PTI (Quentin et al, 2009). Several other hydroxycinnamate derivatives functioning in resistance to A. brassicicola were also recently described (Muroi et al, 2009).…”
Section: Phytoalexins and Other Secondary Metabolitesmentioning
confidence: 99%
“…C6-aldehydes also induce camalexin-accumulation and increased expression of defense-related genes as well as the COMT transcript (Kishimoto et al, 2005;. Arabidopsis COMT, encoding a 5-hydroxyguaiacyl O-methyltransferase involved in lignin biosynthesis, is required for resistance to A. brassicicola and B. cinerea (Quentin et al, 2009). The susceptibility of comt mutants is independent of hormone-mediated defenses and correlates with a signifi cant decrease in sinapoyl malate, a hydroxycinnamate ester also derived from the phenylpropanoid pathway (D'Auria and Gershenzon, 2005;Quentin et al, 2009).…”
Section: Phytoalexins and Other Secondary Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…En plantas de Arabidopsis thaliana en las que se sobre-expresaron las enzimas C4H (enzima temprana en la ruta de los fenilpropanoides) y F5H (enzima que cataliza la hidroxilación irreversible de precursores G hacía la biosíntesis de unidades S), hubo un incremento del 50 % en el contenido de unidades S, en comparación con las plantas silvestres; mientras que la producción de unidades G se inhibió, ocasionando que en las plantas modificadas la reproducción del nematowas not bocked (Wuyts et al, 2006). In contrast to the above, Quentin et al (2009) found that in A. thaliana plants in which the levels of S lignin fell due to the blockage of activity in enzyme COMT, the growth of the nematode and its life cycle were similar to that observed in control plants in which the enzyme was not blocked. However, A. thaliana is, by nature, susceptible to M. incognita, and therefore in this case the differences in the content of lignin monomers (G or S) in the plant tissues did not influence the infection and life cycle of the nematode in A. thaliana, although one cannot exclude the possibility that in other plants, changes in the activity of enzyme COMT can determine the type of interaction (compatible or incompatible) (Pegard et al, 2005).…”
Section: Modifications In the Synthesis And Accumulation Of Lignin Inmentioning
confidence: 99%
“…Lignin, through strengthening the water-conducting cells, contributed to the formation of the efficient long-distance conducting system [12,133]. Furthermore, lignin is one of the most difficult to degrade biopolymers, so that it constitutes an effective protection against pathogens and herbivores, which have been evolving together with vascular plants [134,135].…”
Section: Lignin -Phenol Component Important For Terrestrializationmentioning
confidence: 99%